Pengaruh Kepercayaan Merek dan Kualitas Produk terhadap Keputusan Pembelian AMDK Le Minerale di Kecamatan Medan Petisah - Mikael Meikal Telaumbanua; Witeanus Halawa; Yaatulo Tafonao; Bayu Teta (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2025)
This study aims to analyze the effect of Brand Trust and Product Quality on the Purchase Decision of Bottled Drinking Water (AMDK) brand Le Minerale in Medan Petisah District. The research method used is quantitative with a multiple linear regression approach. The sample consisted of 70 respondents selected using accidental sampling technique. Data were collected through questionnaires and analyzed using validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-test, F-test, and determination test (Adjusted R Square). The results show that Brand Trust and Product Quality have a positive and significant effect both partially and simultaneously on Purchase Decision. The Adjusted R Square value of 0.441 indicates that these two variables explain 44.1% of the variation in purchase decisions, while the remaining 55.9% is influenced by other factors outside the research model.